2018
DOI: 10.1111/cdev.13199
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Child Math Talk About Fractions During Formal Learning and Guided Play Activities

Abstract: This study examined parent–child math talk within three contexts (formal learning; guided play; unguided play) in order to identify characteristics of activities supporting high‐quality math engagement. Seventy‐two dyads of parents and 4‐ and 5‐year‐olds were observed using a set of toy foods; instructions and materials varied across conditions. Parents and children engaged in the most math talk in formal learning; guided play also yielded more math talk than unguided play. Parents rated the formal learning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 40 publications
2
43
0
4
Order By: Relevance
“…These strong relations may potentially explain why the direct + indirect factor was related to all direct assessments. It may be that when parents engage their children in mathematics-focused activities, they may go beyond just explicit teaching and also use significant amounts of math talk (Eason and Ramani, 2020). It is possible that this math talk may expand beyond simple numeracy-related talk to include mathematical language and spatial skills; however, the specific types of talk parents use during these types of activities at home needs to be further investigated.…”
Section: Relations Between the Home Mathematics Environment And Prescmentioning
confidence: 99%
See 1 more Smart Citation
“…These strong relations may potentially explain why the direct + indirect factor was related to all direct assessments. It may be that when parents engage their children in mathematics-focused activities, they may go beyond just explicit teaching and also use significant amounts of math talk (Eason and Ramani, 2020). It is possible that this math talk may expand beyond simple numeracy-related talk to include mathematical language and spatial skills; however, the specific types of talk parents use during these types of activities at home needs to be further investigated.…”
Section: Relations Between the Home Mathematics Environment And Prescmentioning
confidence: 99%
“…Though existing work has not directly linked parent reported HME to mathematical language, there is a growing body of evidence that would support that link. For example, recent evidence in an experimental setting suggests that parent–child interactions that are explicitly focused on teaching mathematics (direct numeracy activities) show greater amounts of math-related talk during these activities than in less direct mathematics-related activities or non-mathematics related activities ( Eason and Ramani, 2020 )—suggesting that when parents are engaged in direct mathematics activities, they are more likely to use (and potentially support) mathematical language compared to when they are engaged in less directed activities. Moreover, the direct activities that parents and children engage in most frequently (e.g., counting and comparing; Thompson et al, 2017 ) involve the numeracy skills that are most closely related to children’s mathematical language knowledge ( Hornburg et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, it is unclear whether short conversations about a variety of academically-relevant concepts or more in-depth conversation about one concept is the critical factor in promoting school readiness through conversations between caregivers and children. Most prior research has examined the effects of the amount of math or shape talk as given by the frequency of occurrence, but there are a few studies that have assessed the variability in the types of words being used in conversation (e.g., Eason and Ramani, 2020 ). The coding scheme for this study was designed to measure conversations about multiple academically-relevant concepts such as numbers, colors, and shapes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study compared the impact of guided play in a sandpit -during which a teacher encouraged young children's exploration and experimentation with various materials -to free play with the same materials [van Schijndel]. Overall, most studies reported that guided play with PMs was more effective than free play with the same or similar materials for children's visual-spatial, language, and exploratory play outcomes [Borriello;Casey 2008a;Eason;Ferrara;Fisher 2011bFisher , 2013.…”
Section: Free Playmentioning
confidence: 99%